CHALLENGES FACE BY YOUTH REGARDING ENTREPRENEURSHIP WITH SPECIAL REFERENCE TO NASHIK DISTRICT - Nikam, Sahebrao Daulat (ShodhKosh: Journal of Visual and Performing Arts, 2024)
outh are the Strength of the country. As per 2011 census nearly 34 percent persons are below the age of 34 years .These people need employments. In India employment growth rate is not in proportion to the population of Young people. Entrepreneurship is solution of unemployment in India. This research paper tries to focus on youth perception toward entrepreneurship and problems of youth.